Regulation of financial markets before and after the global crisis - Peša, Anita Radman; Zubak, Vanja; Mitrović, Duje (Oeconomica Jadertina, 2017)
The banking sector in the global economic system is an area of great impact on the preservation of macroeconomic stability. As it turned out, and during the recent economic crisis, whose consequences are still felt in many countries, the collapse of the financial markets has farreaching effects on all of the national financial markets. The aim of this paper is to analyze the existing regulation of the financial markets and its (lack of) performance in the current financial risk management in order to preserve macroeconomic stability, and provide a secure and stable banking system. The purpose of the study was to present financial regulation before the crisis of 2008 / 2009, and to compare it with the regulations issued after the global crisis of 2008 / 2009 in order to conclusion whether it is cosmetic or real changes of regulating the financial system, and whether existing regulation in the future successfully prevent minor and major disruptions of the financial markets. Croatian financial market is especially analysed in the case of manipulation using the benchmark interest rates.